2018
DOI: 10.4269/ajtmh.17-0526
|View full text |Cite
|
Sign up to set email alerts
|

Bionomics and Spatial Distribution of Triatomine Vectors of Trypanosoma cruzi in Texas and Other Southern States, USA

Abstract: Abstract.Defining spatial and temporal occurrences of triatomine vectors of Trypanosoma cruzi, the agent of Chagas disease, in the US is critical for public health protection. Through a citizen science program and field collections from 2012 to 2016, we collected 3,215 triatomines, mainly from Texas. Using morphological and molecular approaches, we identified seven Triatoma species and report sex, length, and blood engorgement status. Many citizen-collected triatomines (92.9%) were encountered indoors, in peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 44 publications
0
73
0
Order By: Relevance
“…(Kjos et al, 2008;Curtis-Robles et al, 2018a), with discrete typing units (DTU) TcI and TcIV most commonly represented (Roellig et al, 2013;Brenière et al, 2016;Curtis-Robles et al, 2018a). Although triatomines found in the United States are generally considered sylvatic, these vectors are regularly encountered in and around human dwellings (Kjos et al, 2008;Wozniak et al, 2015;Curtis-Robles et al, 2018b). Wildlife and domestic canines are infected with T. cruzi throughout Texas and across the southern United States (Beard et al, 2003;Kjos et al, 2008;Brown et al, 2010;Curtis-Robles et al, 2017;Hodo and Hamer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(Kjos et al, 2008;Curtis-Robles et al, 2018a), with discrete typing units (DTU) TcI and TcIV most commonly represented (Roellig et al, 2013;Brenière et al, 2016;Curtis-Robles et al, 2018a). Although triatomines found in the United States are generally considered sylvatic, these vectors are regularly encountered in and around human dwellings (Kjos et al, 2008;Wozniak et al, 2015;Curtis-Robles et al, 2018b). Wildlife and domestic canines are infected with T. cruzi throughout Texas and across the southern United States (Beard et al, 2003;Kjos et al, 2008;Brown et al, 2010;Curtis-Robles et al, 2017;Hodo and Hamer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that vector distributions are influenced by climate, land cover 100 types and rural/urban classifications [19][20][21][22][23][24]. Environmental variables for these three 101 data types were obtained at a nominal resolution of 5 × 5 kilometres.…”
Section: Environmental Variables 99mentioning
confidence: 99%
“…Earlier studies [19,20,22,23,25], most notably [24], have modelled the distributions 279 of some of these species but only in specific regions, states or countries. Additionally, 280 comparisons with the previous work are limited because of differences in methodology, 281 data sets and spatial extent under consideration.…”
mentioning
confidence: 99%
“…cruzi is transmitted through the introduction of infected triatomine feces through the bite site or mucous membrane, or orally through ingestion of the triatomines or their feces. The most commonly encountered triatomine in south-central Texas is Triatoma gerstaeckeri [20][21][22]. T. gerstaeckeri is frequently found in and around dog kennels and other peridomestic structures and has shown high rates of infection with T. cruzi [14,20,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly encountered triatomine in south-central Texas is Triatoma gerstaeckeri [20][21][22]. T. gerstaeckeri is frequently found in and around dog kennels and other peridomestic structures and has shown high rates of infection with T. cruzi [14,20,22,23]. After an animal is exposed the trypomastigote invades the mammalian host cells [24], where T. cruzi has a tissue tropism for cardiomyocytes and skeletal muscle [25].…”
Section: Introductionmentioning
confidence: 99%